Technical considerations for circulating tumor DNA detection in oncology. (1st February 2019) - Franczak, Claire; Filhine-Tresarrieu, Pierre; Gilson, Pauline; Merlin, Jean-Louis; Au, Lewis; Harlé, Alexandre
ABSTRACT: Introduction : Blood draw or collection of other body fluids, known as 'liquid biopsies' are generally less invasive procedures than tumor biopsies. Cell-free tumor DNA (ctDNA) is widely evaluated in cancer for early detection, diagnosis, prognosis, therapy monitoring or determination of minimal residual disease. In body fluid samples, ctDNA can represent a small fraction of total cell-free DNA (cfDNA), requiring highly sensitive assays. Areas covered : The first part of this review is dedicated to critical preanalytical points necessary to obtain suitable samples for cfDNA analysis. The second part describes the available techniques for ctDNA analysis. Expert commentary : Detection of ctDNA is emerging as a powerful adjunct in the management of patients with cancer. For reliable ctDNA detection, preanalytical steps from sampling to DNA extraction are crucial. Various techniques are available for cfDNA detection, but one needs to consider the appropriate application for the patient's clinical trajectory, whether it is for diagnosis or disease monitoring. Broad screening assays like Next-Generation Sequencing should be used for early cancer detection or for tumor molecular characterization to guide therapy options in a molecular board context. Techniques designed for unique hotspot or well-identified mutations are the most sensitive and should be used for monitoring purposes.